2014
DOI: 10.1055/s-0034-1371866
|View full text |Cite
|
Sign up to set email alerts
|

Can Valproic Acid be an Inducer of Clozapine Metabolism?

Abstract: Introduction Prior clozapine studies indicated no effects, mild inhibition or induction of valproic acid (VPA) on clozapine metabolism. The hypotheses that 1) VPA is a net inducer of clozapine metabolism, and 2) smoking modifies this inductive effect were tested in a therapeutic drug monitoring study. Methods After excluding strong inhibitors and inducers, 353 steady-state total clozapine (clozapine plus norclozapine) concentrations provided by 151 patients were analyzed using a random intercept linear model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 51 publications
(123 reference statements)
1
28
0
Order By: Relevance
“…Norclozapine has biological activity (Li et al, 2005; Olianas et al, 2009; Weiner et al, 2004) and clinicians sometimes measure the sum of clozapine and norclozapine as a “total clozapine” level (total clozapine level is shown in Figure 1a) (Diaz et al, 2014). We observed no significant differences in the DPVs between clozapine and norclozapine (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Norclozapine has biological activity (Li et al, 2005; Olianas et al, 2009; Weiner et al, 2004) and clinicians sometimes measure the sum of clozapine and norclozapine as a “total clozapine” level (total clozapine level is shown in Figure 1a) (Diaz et al, 2014). We observed no significant differences in the DPVs between clozapine and norclozapine (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The author has been conducting PubMed searches in this area for more than 15 years in the process of publishing 1) review articles in this area, [3][4][5][6][7][8][9] 2) studies of the effects of AED inducers in psychiatry, [10][11][12][13][14][15][16][17][18][19] and 3) a book with practical guidelines for each AED and/or mood stabilizing agent; the book has more than 1000 different references. 20 All of these were published in the context of trying to develop a comprehensive model of personalized prescription in psychiatry.…”
Section: Literature Searchmentioning
confidence: 99%
“…More recently, information on its inductive properties has been accumulating. VPA induces: 1) its own metabolism by inducing β-oxidation (prospective study); 102 2) CYP3A4 and P-gp gene expression (in vitro study); 103 3) possible UGT1A1 in a patient taking irinotecan (which has an active metabolite SN-38 metabolized by UGT1A1); 104 4) aripiprazole metabolism to a mild degree (prospective study), 105 5) olanzapine metabolism (case series, 106 TDM, 107 and a prospective DI study); 15 6) clozapine metabolism (case series, 108-109 prospective case, 18 and statistical model on TDM-DI studies 14,19 ); and 6) vitamin D metabolism in an in vitro study. 110 The available information on clozapine-olanzapine metabolism indicates that VPA can be an inducer and/or a competitive inhibitor.…”
Section: Vpamentioning
confidence: 99%
“…3 Valproate-clozapine pharmacokinetic interactions should be borne in mind where previous studies have showed no effect, mild inhibition, or induction of clozapine metabolism. 4 Moreover, dynamic interactions including myelosuppression, oversedation and confusion, and metabolic derangement have been reported in literature. 5 Nonetheless, mechanistically, valproate is GABA potentiator.…”
Section: Dear Sirmentioning
confidence: 99%